Pengaruh E-Commerce Terhadap Peningkatan Omzet UMKM Bermitra Grab di Kabupaten Garut - Nurlaela, Lina; Syakinah, Fitri (Jurnal Algoritma, 2025)
Web technology has become an integral part of the e-commerce infrastructure implemented by MSME players. Through e-commerce, buyers can purchase or check products offered anytime and anywhere. However, they often find it difficult to understand digital marketing strategies, such as SEO (Search Engine Optimization), social media marketing, and seeing competition that can help increase sales. Therefore, an analysis of the factors influencing sales growth is needed. This study aims to analyze the impact of e-commerce on revenue growth for SMEs partnering with Grab. The method used is descriptive quantitative analysis, and data analysis employs Structural Equation Modeling Partial Least Squares (SEM-PLS) with a sample of 100 respondents. The research data uses primary data collected through a questionnaire. The questionnaire was distributed to SMEs partnered with Grab. The results of this study prove that e-commerce has a significant impact on revenue growth.